Efforts to Improve Bullet Shot Learning Outcomes Through the Circuit Method and Tool Modifications for Middle School Middle School 3 Percut Sei Tuan Academic Year 2021/2022 - Dedy Asmajaya (Jurnal Pendidikan Jasmani (JPJ), 2022)
This research is a class action research (Classroom Action Research) with implementation stages including planning, action, observation, and reflection. The location of this research was carried out in class VIII SMP N 3 Percut Sei Tuan. Classroom action research has a very important and strategic role in improving the quality of learning if it is implemented properly, meaning that the parties involved in PTK (teachers) try to consciously develop the ability to detect and solve problems or improve situations and carefully observe their implementation to measure the level of the success of learning that is held professionally. In cycle I, 20 students (59%) declared complete and 14 students (49%) did not complete their studies and in cycle II, 30 students (88%) declared complete and 4 students (12%) did not complete. ) has achieved classical mastery learning and the average learning process of students in the first cycle is 71.62 and in the second cycle the average learning process increases to 84.07. As for the increase in learning outcomes from the initial data to cycle I, 3% with an average increase in learning outcomes 3 the increase from cycle I to cycle II was 12.45% with an average increase in learning outcomes of 77.23.